Disfungsi Transmisi Linguistik Intra-Keluarga: Hambatan Sosial dan Kultural dalam Pelestarian Bahasa Daerah Suku Wayoli di Tulehu, Maluku - Lestaluhu, Sheila Firdayanti; Sopacua, Yustina (Populis: Jurnal Ilmu Sosial dan Ilmu Politik, 2024)
This study examines the dysfunction of intra-familial linguistic transmission as a key factor in the decline of indigenous languages, focusing on the Wayoli ethnic group in Tulehu, Central Maluku. It explores socio-cultural barriers that hinder language preservation, particularly within family communication. Using a qualitative approach, data were collected through observation, in-depth interviews, and documentation. Findings reveal that indigenous language use is largely limited to older family members or occurs only between spouses. Children, as the next generation, are not actively involved in using the language, resulting in a discontinuity of transmission. Major obstacles include semantic barriers—children’s inability to understand the language; psychological barriers—parents' fear that using local language may impede their children’s mastery of Indonesian; and socio-institutional barriers—such as the weak role of traditional leaders and the absence of indigenous language education in schools. These dynamics point to a broader pattern of linguistic neglect rooted in structural and cultural shifts. This study contributes to the discourse on language endangerment by highlighting the need to revitalize the roles of family and educational institutions as agents of linguistic sustainability. It recommends collaborative strategies involving families, cultural leaders, and schools to reintegrate local languages into everyday life and the educational curriculum.